PENGARUH KECERDASAN EMOSIONAL TERHADAP PERILAKU KEWARGAAN ORGANISASIONAL YANG DIMEDIASI OLEH KUALITAS KEHIDUPAN KERJA PEGAWAI KONTRAK KANTOR DINAS PENGAIRAN ACEH - Amallia Zahara, Fairuzzzabadi (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2018)
Abstract: This study aims to measure the effect of Emotional Intelligence to contract employee’s Organizational Citizenship Behavior in irrigation’s office of Aceh with Quality Working of Life as mediating variable. The sample used in this study were contract employee is totaling 83 respondents. The sampling technique used is Simple Random Sampling. Hierarchical Linear Modelling (HLM) was used as a method of analysis to determine the effect to fall the variables involved. Based on the results of HLM analysis indicated that Emotional Intelligence was related to Organizational Citizenship Behavior, Emotional Intelligence positively influence Quality Working of Life, while Quality Working of Life was unrelated to Organizational Citizenship Behavior, and Quality Working of Life doesn’t mediate relationship between Emotional Intelligence and Organizational Citizenship Behavior.